INTERAKSI DINAMIS ANTARA PERPUTARAN MODAL KERJA DAN PERPUTARAN PIUTANG TERHADAP RETURN ON ASSET (ROA) - Furniawan, Furniawan (The Asia Pacific Journal Of Management Studies, 2023)
Financial performance of a company can be influenced by various factors, including working capital management and receivables management. This research aims to examine the interaction between working capital, receivables, and return on assets (ROA) as a key indicator of financial health. Through a statistical analysis approach, financial data from several companies have been collected and analyzed to understand potential relationships. The study evaluates the influence of working capital on the ROA of a company. This analysis identifies the extent to which working capital management can affect the profitability of an entity. Furthermore, the interaction between receivables management and ROA is explored. The  research aims to measure how receivables management policies can strengthen or undermine the financial performance of a company. The results of the research are expected to provide new insights into corporate financial strategies and offer a deep understanding of the importance of working capital and receivables management in achieving optimal asset returns. The findings of this research are expected to serve as a foundation for companies to enhance operational efficiency and optimize the allocation of financial resources.